Glix 13, a New Drug Acting on Glutamatergic Pathways in Children and Animal Models of Autism Spectrum Disorders. (30th January 2014) - Santini, Annamaria Chiara; Pierantoni, Giovanna Maria; Gerlini, Raffaele; Iorio, Rosamaria; Olabinjo, Yinka; Giovane, Alfonso; Di Domenico, Marina; Sogos, Carla
Abstract : Recently standardized diagnostic instruments have been developed in diagnostic and therapeutic procedures for Autism Spectrumv Disorders (ASD). According to the DSM-5 criteria, individuals with ASD must show symptoms from early childhood. These symptoms are communication deficits and restricted, repetitive patterns of behaviour. It was recently described by Bioinformatic analysis that 99 modified genes were associated with human autism. Gene expression patterns in the low-line animals show significant enrichment in autism-associated genes and the NMDA receptor gene family was identified among these. Using ultrasonic vocalizations, it was demonstrated that genetic variation has a direct impact on the expression of social interactions. It has been proposed that specific alleles interact with a social reward process in the adolescent mouse modifying their social interaction and their approach toward each other. In this review we report that the monoclonal antibody-derived tetrapeptide GLYX-13 was found to act as an N-methyl-D-aspartate receptor modulator and possesses the ability to readily cross the blood brain barrier. Treatment with the NMDAR glycine site partial agonist GLYX-13 rescued the deficit in the animal model. Thus, the NMDA receptor has been shown to play a functional role in autism, and GLYX-13 shows promise for the treatment of autism in autistic children.